Solid electrolyte membrane and preparation method thereof, and all-solid-state battery
By using the grinding and mixing and dry forming process of additives such as oxide solid electrolyte and polyvinylidene fluoride in the solid electrolyte membrane, the energy density bottleneck and safety of lithium-ion batteries are solved, and the ionic conductivity of the solid electrolyte membrane is improved. Mechanical strength improves the performance of all solid-state batteries.
Patent Information
- Application Number
- CN202410992454.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-07-23
AI Technical Summary
The energy density of traditional lithium-ion batteries is close to the bottleneck value, and the poor compatibility of metal lithium with liquid electrolytes leads to safety problems. The ionic conductivity of common solid electrolytes is relatively low.
The oxide solid electrolyte is used to grind and mix with polyvinylidene fluoride and its copolymers, lithium salts and ionic liquids and other additives. The ceramic electrolyte membrane is prepared through dry molding process, and the polytetrafluoroethylene content is controlled to be between 0.49 wt% and 5.03 wt% , to improve the ionic conductivity and mechanical strength of the ceramic electrolyte membrane.
It significantly improves the ionic conductivity and mechanical strength of the solid electrolyte membrane, solves lithium dendrites and safety problems, and improves the performance of all-solid state batteries.
Smart Images

Figure CN118553987B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid-state battery technology, and specifically to a solid-state electrolyte membrane, a method for preparing a solid-state electrolyte membrane, and an all-solid-state battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, the requirements for the energy density of power batteries are getting higher and higher, while the energy density of traditional lithium-ion batteries has reached a bottleneck value, and the development of new lithium battery systems has become an urgent need. Replacing the graphite negative electrode of lithium-ion batteries with metallic lithium can significantly increase the energy density of the battery and reduce the volume of the battery. However, metallic lithium has poor compatibility with liquid electrolytes, and metallic lithium is prone to form dendrites during repeated charging and discharging, which can easily puncture the diaphragm and cause safety problems. By replacing liquid electrolytes with solid electrolytes, the problem of lithium dendrites can be alleviated to a certain extent, but common solid electrolytes have the problem of low ionic conductivity. Summary of the invention
[0003] The embodiments of the present application provide a solid electrolyte membrane and a preparation method thereof, as well as an all-solid-state battery, which can improve the technical problem of low ionic conductivity of solid electrolytes.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a solid electrolyte membrane, comprising:
[0005] Performing a first grinding and mixing process on the oxide solid electrolyte and the additive to obtain a first mixture, wherein the additive includes at least one of a first additive and a second additive, the first additive includes at least one of polyvinylidene fluoride and a copolymer thereof, and the second additive includes a lithium salt and an ionic liquid;
[0006] The first mixture and polytetrafluoroethylene are subjected to a second grinding and mixing process to obtain a flake mixture, wherein the content of the polytetrafluoroethylene is 0.49wt% to 5.03wt% based on the total mass of the flake mixture;
[0007] The sheet-shaped mixed material is subjected to a rolling process to obtain a ceramic electrolyte membrane, and the solid electrolyte membrane includes the ceramic electrolyte membrane.
[0008] In one embodiment, the additive includes the first additive and the second additive, and the first grinding and mixing treatment of the oxide solid electrolyte and the additive to obtain the first mixture includes: grinding and mixing the oxide solid electrolyte and the first additive to obtain a dry mixture; grinding and mixing the dry mixture with the second additive to obtain the first mixture.
[0009] In one embodiment, the preparation process of the dry mixture further includes: grinding and mixing the oxide solid electrolyte and carboxymethyl cellulose.
[0010] In one embodiment, based on the total mass of the flaky mixture, the content of the oxide solid electrolyte is 80wt%~92wt%, the content of the first additive is 2.29wt%~5.71wt%, the content of the second additive is 1.71wt%~4.29wt%, and the content of the carboxymethyl cellulose is 2.86wt%~7.14wt%.
[0011] In one embodiment, in the second additive, the lithium salt includes lithium bis(trifluoromethyl)sulfonyl imide, the ionic liquid includes N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and the mass ratio of the lithium bis(trifluoromethyl)sulfonyl imide to the N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt is (1.5~2.5):1.
[0012] In one embodiment, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium gallium oxide and lithium lanthanum zirconium tantalum oxide.
[0013] In one embodiment, the temperature of the roller pressing treatment is 50° C. to 100° C., and the roller pressing pressure is 15t to 40t.
[0014] In one embodiment, the method for preparing the solid electrolyte membrane further comprises preparing a polymer electrolyte membrane by a wet forming process, wherein the polymer electrolyte membrane is located on one side surface of the ceramic electrolyte membrane.
[0015] In the second aspect, an embodiment of the present application also provides a solid electrolyte membrane, including a ceramic electrolyte membrane, wherein the ceramic electrolyte membrane includes an oxide solid electrolyte, an additive and polytetrafluoroethylene, the additive includes at least one of a first additive and a second additive, the first additive includes at least one of polyvinylidene fluoride and a copolymer of polyvinylidene fluoride, the second additive includes a lithium salt and an ionic liquid, and based on the total mass of the ceramic electrolyte membrane, the content of the polytetrafluoroethylene is 0.49wt%~5.03wt%.
[0016] In one embodiment, the additive includes the first additive and the second additive, and the ceramic electrolyte membrane also includes carboxymethyl cellulose. Based on the total mass of the ceramic electrolyte membrane, the content of the oxide solid electrolyte is 80wt%~92wt%, the content of the first additive is 2.29wt%~5.71wt%, the content of the second additive is 1.71wt%~4.29wt%, and the content of the carboxymethyl cellulose is 2.86wt%~7.14wt%.
[0017] In one embodiment, in the ceramic electrolyte membrane, the lithium salt includes lithium bis(trifluoromethyl)sulfonyl imide, the ionic liquid includes N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, and the mass ratio of the lithium bis(trifluoromethyl)sulfonyl imide to the N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide is (1.5~2.5):1.
[0018] In one embodiment, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium gallium oxide and lithium lanthanum zirconium tantalum oxide.
[0019] In one embodiment, the thickness of the ceramic electrolyte membrane is 20 μm-40 μm.
[0020] In one embodiment, the solid electrolyte membrane further comprises a polymer electrolyte membrane, the polymer electrolyte membrane is located on one side surface of the ceramic electrolyte membrane, and the thickness of the polymer electrolyte membrane is 10 μm to 20 μm.
[0021] In a third aspect, an embodiment of the present application also provides an all-solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte membrane, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode, and the solid electrolyte membrane is the above-mentioned solid electrolyte membrane.
[0022] Beneficial effects of the embodiments of the present application:
[0023] The solid electrolyte membrane provided in the embodiment of the present application includes a ceramic electrolyte membrane, which includes an oxide solid electrolyte, an additive and polytetrafluoroethylene, wherein the additive includes at least one of lithium salt + ionic liquid, polyvinylidene fluoride and its copolymers, and the additive is dispersed in the oxide solid electrolyte, which can effectively construct an ion transmission channel and improve the ionic conductivity of the ceramic electrolyte membrane; polytetrafluoroethylene is used as a binder, and by controlling the content of polytetrafluoroethylene in the total material to 0.49wt%~5.03wt%, it can not only ensure film formation but also help to improve the mechanical strength of the ceramic electrolyte membrane, thereby improving the mechanical strength of the solid electrolyte membrane.
[0024] In the preparation method of the solid electrolyte membrane, a ceramic electrolyte membrane is prepared by adopting a dry forming process, which is beneficial to ensure the density of the ceramic electrolyte membrane and improve the mechanical strength of the ceramic electrolyte membrane. The solid electrolyte membrane includes the ceramic electrolyte membrane, so that the mechanical strength of the solid electrolyte membrane is improved. Specifically, the ceramic electrolyte membrane is obtained by grinding and mixing the oxide solid electrolyte, additives and polytetrafluoroethylene and then rolling them, wherein the additive is used to improve the ionic conductivity of the ceramic electrolyte membrane, and polytetrafluoroethylene is used as a binder. By controlling the content of polytetrafluoroethylene in the total material to 0.49wt%~5.03wt%, it can not only ensure the film formation but also help to improve the mechanical strength of the ceramic electrolyte membrane. More specifically, the oxide solid electrolyte and additives are first subjected to a first grinding and mixing treatment to form a first mixture, the first mixture and polytetrafluoroethylene are then subjected to a second grinding and mixing treatment to form a flaky mixture, and finally the flaky mixture is rolled to form a ceramic electrolyte membrane, wherein the first grinding and mixing treatment is used to promote uniform mixing of the oxide solid electrolyte and the additive to enhance the dispersion effect of the additive, the second grinding and mixing treatment is used to promote the fiberization of polytetrafluoroethylene to achieve film formation, the first grinding and mixing treatment and the second grinding and mixing treatment are independent of each other, reducing the adverse effects of polytetrafluoroethylene fiberization on the dispersion effect of the additive, and effectively improving the homogenization of the material, so that the material finally becomes dense after the rolling treatment to form a continuous lithium ion transmission channel, which is beneficial to improving the ionic conductivity of the ceramic electrolyte membrane, and then improving the ionic conductivity of the solid electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a flow chart of a method for preparing a solid electrolyte membrane provided in an embodiment of the present application;
[0027] Figure 2 is a scanning electron microscope image of the ceramic electrolyte membrane provided in Example 2 of the present application;
[0028] Figure 3 This is a scanning electron microscope image of the ceramic electrolyte membrane provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0030] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of a device in actual use or working state; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0031] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0032] In this application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0033] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0034] First, see Figure 1, an embodiment of the present application provides a method for preparing a solid electrolyte membrane. The solid electrolyte membrane includes a ceramic electrolyte membrane. It should be noted here that the solid electrolyte membrane can be a single-layer membrane structure including only a ceramic electrolyte membrane, the solid electrolyte membrane can also be a multi-layer membrane structure including multiple layers of ceramic electrolyte membranes, and the solid electrolyte membrane can also be a composite membrane structure including a ceramic electrolyte membrane and a polymer electrolyte membrane, which is not limited here.
[0035] Specifically, the preparation method of the solid electrolyte membrane includes preparing a ceramic electrolyte membrane by a dry forming process. The dry forming process does not use an organic solvent, so it can prevent the volatilization of the organic solvent and the generation of pores, thereby improving the density of the ceramic electrolyte membrane and further improving the ionic conductivity of the ceramic electrolyte membrane. The process of preparing a ceramic electrolyte membrane by a dry forming process includes:
[0036] S1. Perform a first grinding and mixing process on the oxide solid electrolyte and the additive to obtain a first mixture.
[0037] Compared with polymer electrolytes, oxide solid electrolytes have higher ionic conductivity, wider electrochemical stability window, good thermal stability, chemical stability and mechanical strength, which are beneficial to improving the performance of ceramic electrolyte membranes. Optionally, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium gallium oxide (LLZGO) and lithium lanthanum zirconium tantalum oxide (LLZTO). LLZO is garnet type with the chemical formula Li7La3Zr2O 12 LLZGO is LLZO doped with Ga, and LLZTO is LLZO doped with Ta.
[0038] The above-mentioned additives mainly refer to additives for improving the ionic conductivity of the ceramic electrolyte membrane. In detail, the additive includes at least one of a first additive and a second additive. Exemplarily, the additive includes a first additive, or the additive includes a second additive, or the additive includes a first additive and a second additive. Among them, the first additive includes at least one of polyvinylidene fluoride and a copolymer of polyvinylidene fluoride. The copolymer of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride has a high dielectric constant, which is beneficial to enhance the ion transportability of the ceramic electrolyte membrane. As an example, the copolymer of polyvinylidene fluoride includes polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The second additive includes a lithium salt and an ionic liquid. As an example, the lithium salt can be dissolved in an ionic liquid. The lithium salt can increase the lithium salt content in the ceramic electrolyte membrane, making the ionic conductivity of the ceramic electrolyte membrane higher. The ionic liquid itself has a high ionic conductivity and can also improve the ionic conductivity of the ceramic electrolyte membrane. When the lithium salt is dissolved in the ionic liquid, the ionic liquid has a certain wetting effect, which is beneficial to promote the lithium salt to be uniformly dispersed in the oxide solid electrolyte. As an example, the lithium salt includes at least one of lithium bis(trifluoromethyl)sulfonyl imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(perfluoroethylsulfonyl)imide (LIBETI) and lithium bis(oxalate)borate (LiBOB). As an example, the ionic liquid is a pyrrole ionic liquid, such as N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid. Optionally, in the second additive, the lithium salt is LiTFSI, the ionic liquid is N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid, and the mass ratio of LiTFSI to N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid is (1.5~2.5):1. For example, the mass ratio of LiTFSI to N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid is 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1.
[0039] Usually, the first grinding and mixing treatment includes a grinding process, that is, adding the oxide solid electrolyte and the additive together, and grinding them, so that the additive can be more evenly dispersed in the oxide solid electrolyte, improving homogenization, which is conducive to forming a continuous ion transmission path and improving the ion conductivity of the ceramic electrolyte membrane. Especially when the additive includes the first additive, since no organic solvent is used in the dry molding process, the first additive is difficult to dissolve. In this case, the first additive relies more on the grinding process to improve the dispersion effect.
[0040] In some embodiments, when the additive includes a first additive and a second additive, step S1 specifically includes:
[0041] S11, grinding and mixing the oxide solid electrolyte and the first additive to obtain a dry mixture;
[0042] S12, grinding and mixing the dry blend and the second additive to obtain a first mixture.
[0043] That is, the first additive is first ground and mixed with the oxide solid electrolyte, and then the second additive is ground and mixed with the oxide solid electrolyte. By grinding and mixing in steps, the influence of the liquid second additive on the dispersion effect of the solid first additive is reduced. Since the oxide solid electrolyte and the first additive are usually dry powders, the two are mixed to form a dry blend. In other embodiments, the first mixture can also be prepared by synchronous grinding and mixing, that is, the oxide solid electrolyte, the first additive and the second additive are added together and ground together.
[0044] In some embodiments, carboxymethyl cellulose is further added during the preparation of the ceramic electrolyte membrane, specifically, carboxymethyl cellulose is added before the second additive is added. In other words, the dry mix also contains carboxymethyl cellulose. In detail, step S1 further includes:
[0045] S13, grinding and mixing the oxide solid electrolyte and carboxymethyl cellulose.
[0046] Here, S11 and S13 are included in the preparation process of the dry mix. In step S1, the order of S11, S12 and S13 can be: S11→S13→S12, or S13→S11→S12, or (S11+S13)→S12.
[0047] As an example, the first grinding and mixing process can be performed at room temperature without additional temperature conditions, and the conditions are simple and convenient, which is conducive to reducing production costs. The grinding method of the first grinding and mixing process can be manual grinding or machine grinding.
[0048] Specifically, the process of preparing the ceramic electrolyte membrane by the dry forming process also includes:
[0049] S2, performing a second grinding and mixing process on the first mixture and polytetrafluoroethylene to obtain a flaky mixed material.
[0050] The embodiment of the present application uses polytetrafluoroethylene (PTFE) as a binder, because polytetrafluoroethylene can be ground in the absence of an organic solvent so that polytetrafluoroethylene and grinding media (such as grinding balls and blades) collide and rub against each other, generating shear force, and polytetrafluoroethylene undergoes fiberization to form polytetrafluoroethylene fibers, which can wrap around other particles in the first mixture to achieve film formation. Although the materials have been initially bonded to form membranes at this stage, they are still mainly small dispersed membranes, and it is difficult to form a continuous large-area membrane layer, that is, the obtained material is a flaky mixture.
[0051] Usually, the composition of the sheet mixture determines the composition of the final ceramic electrolyte membrane. The content of polytetrafluoroethylene in the sheet mixture affects the mechanical properties and ionic conductivity of the ceramic electrolyte membrane. If the content of polytetrafluoroethylene in the sheet mixture is too high, it is not conducive to the transmission of ions in the ceramic electrolyte membrane. If the content of polytetrafluoroethylene in the sheet mixture is too low, the mechanical strength of the ceramic electrolyte membrane will decrease, or even fail to form a membrane. Based on the total mass of the sheet mixture, the content of polytetrafluoroethylene is 0.49wt%~5.03wt%. Within this range, the ceramic electrolyte membrane can form a good film and has both good mechanical strength and ionic conductivity. As an example, the content of polytetrafluoroethylene is 0.49wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.03wt%. In addition, if the content of polytetrafluoroethylene in the sheet mixture is too high, it will easily cause side reactions after the ceramic electrolyte membrane is assembled into a solid-state battery, resulting in a decrease in the cycle performance of the solid-state battery.
[0052] In some embodiments, based on the total mass of the flaky mixture, the content of the oxide solid electrolyte is 80wt% to 92wt%. Generally, the mechanical strength and ionic conductivity of the ceramic electrolyte membrane increase with the increase of the content of the oxide solid electrolyte, but the excessive content of the oxide solid electrolyte will lead to a decrease in the content of other components, and the final result is that the performance of the ceramic electrolyte membrane deteriorates. As an example, the content of the oxide solid electrolyte is 80wt%, 82wt%, 84wt%, 86wt%, 88wt%, 90wt% or 92wt%.
[0053] In some embodiments, based on the total mass of the flaky mixture, the content of the first additive is 2.29wt%~5.71wt%, and the content of the second additive is 1.71wt%~4.29wt%. The first additive and the second additive are mainly used to improve the ionic conductivity of the ceramic electrolyte membrane. As an example, the content of the first additive is 2.29wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt% or 5.71wt%; the content of the second additive is 1.71wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt% or 4.29wt%.
[0054] In some embodiments, based on the total mass of the sheet mixture, the content of carboxymethyl cellulose is 2.86wt% to 7.14wt%. Carboxymethyl cellulose is mainly used to assist film formation and improve the ductility of the film material during the subsequent rolling process. As an example, the content of carboxymethyl cellulose is 2.86wt%, 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt% or 7.14wt%.
[0055] As an example, the second grinding and mixing process can be performed at room temperature without additional temperature conditions, and the conditions are simple and convenient, which is conducive to reducing production costs. The grinding method of the second grinding and mixing process can be manual grinding or machine grinding.
[0056] Specifically, the process of preparing the ceramic electrolyte membrane by the dry forming process also includes:
[0057] S3. Roll-pressing the flaky mixture to obtain a ceramic electrolyte membrane.
[0058] The purpose of the roller pressing process is to make the sheet-like mixture form a larger continuous membrane layer, that is, a ceramic electrolyte membrane. In addition, the roller pressing process can also improve the density of the ceramic electrolyte membrane and effectively form a continuous lithium ion transmission channel. Optionally, the temperature of the roller pressing process is 50°C~100°C. At this temperature, polytetrafluoroethylene will soften appropriately, which is beneficial to improve the ductility of the sheet-like mixture and to form a large area of ceramic electrolyte membrane. As an example, the temperature of the roller pressing process is 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.
[0059] As an example, the sheet-like mixture is subjected to roller pressing, which includes passing the sheet-like mixture through a gap between two hot pressing rollers and forming the sheet-like mixture, and the gap width between the two hot pressing rollers is 20 μm to 40 μm. It is understood that the gap width between the two hot pressing rollers will affect the thickness of the obtained ceramic electrolyte membrane. When the gap width between the two hot pressing rollers is 20 μm to 40 μm, the thickness of the prepared ceramic electrolyte membrane is 20 μm to 40 μm. As an example, the thickness of the ceramic electrolyte membrane is 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. Optionally, the roller pressing process includes vertical roller pressing and horizontal roller pressing, and the roller pressing pressure of the vertical roller pressing process is 15 t to 40 t, and the roller pressing pressure of the horizontal roller pressing process is 15 t to 40 t.
[0060] The solid electrolyte membrane provided in the embodiment of the present application includes a ceramic electrolyte membrane. In the preparation method of the solid electrolyte membrane, the ceramic electrolyte membrane is prepared by adopting a dry forming process, which is beneficial to ensure the density of the ceramic electrolyte membrane. Specifically, the ceramic electrolyte membrane is obtained by grinding and mixing the oxide solid electrolyte, the additive and the polytetrafluoroethylene and then rolling them, wherein the additive is used to improve the ionic conductivity of the ceramic electrolyte membrane, and the polytetrafluoroethylene is used as a binder. By controlling the content of polytetrafluoroethylene in the total material to 0.49wt%~5.03wt%, it can not only ensure the film formation but also help to improve the mechanical strength of the ceramic electrolyte membrane. More specifically, the oxide solid electrolyte and additives are first subjected to a first grinding and mixing treatment to form a first mixture, the first mixture and polytetrafluoroethylene are then subjected to a second grinding and mixing treatment to form a flaky mixture, and finally the flaky mixture is rolled to form a ceramic electrolyte membrane, wherein the first grinding and mixing treatment is used to promote uniform mixing of the oxide solid electrolyte and the additive to enhance the dispersion effect of the additive, the second grinding and mixing treatment is used to promote the fiberization of polytetrafluoroethylene to achieve film formation, the first grinding and mixing treatment and the second grinding and mixing treatment are independent of each other, reducing the adverse effects of polytetrafluoroethylene fiberization on the dispersion effect of the additive, and effectively improving the homogenization of the material, so that the material finally becomes dense after the rolling treatment to form a continuous lithium ion transmission channel, which is beneficial to improving the ionic conductivity of the ceramic electrolyte membrane, and then improving the ionic conductivity of the solid electrolyte membrane.
[0061] In addition, in some embodiments, the method for preparing the solid electrolyte membrane further includes: preparing a polymer electrolyte membrane, and combining the polymer electrolyte membrane with the ceramic electrolyte membrane. That is, the solid electrolyte membrane also includes the polymer electrolyte membrane, and the polymer electrolyte membrane is located on one side surface of the ceramic electrolyte membrane.
[0062] Optionally, a polymer electrolyte membrane is prepared by a wet forming process, and the polymer electrolyte membrane is located on one side surface of the ceramic electrolyte membrane to obtain a solid electrolyte membrane. Here, the ceramic electrolyte membrane and the polymer electrolyte membrane may be prepared separately and then stacked together; or the ceramic electrolyte membrane may be prepared first and then the polymer electrolyte membrane may be formed on one side surface of the ceramic electrolyte membrane.
[0063] As an example, a polymer, a lithium salt and an organic solvent are mixed to form a slurry, and the slurry is coated on one surface of a ceramic electrolyte membrane. After the slurry is cured, a polymer electrolyte membrane is formed, thereby obtaining a solid electrolyte membrane.
[0064] When the above-mentioned solid electrolyte membrane is applied to a solid-state battery, the polymer electrolyte membrane can correspond to the negative electrode of the solid-state battery. Compared with the ceramic electrolyte membrane, the polymer electrolyte membrane has good flexibility and can effectively build a stable negative electrode-electrolyte interface. The ceramic electrolyte membrane corresponds to the positive electrode of the solid-state battery. Since the voltage window of the ceramic electrolyte membrane is high, it can effectively alleviate the deterioration of the positive electrode interface under the high voltage of the positive electrode. Therefore, the solid electrolyte membrane formed by combining the polymer electrolyte membrane and the ceramic electrolyte membrane helps to improve the cycle stability of the solid-state battery.
[0065] In the second aspect, an embodiment of the present application also provides a solid electrolyte membrane, including a ceramic electrolyte membrane, the ceramic electrolyte membrane includes an oxide solid electrolyte, an additive and polytetrafluoroethylene, the additive includes at least one of a first additive and a second additive, the first additive includes at least one of polyvinylidene fluoride and a copolymer of polyvinylidene fluoride, the second additive includes a lithium salt and an ionic liquid, and based on the total mass of the ceramic electrolyte membrane, the content of polytetrafluoroethylene is 0.49wt%~5.03wt%.
[0066] It should be noted here that the solid electrolyte membrane can be a single-layer membrane structure including only a ceramic electrolyte membrane, or a multi-layer membrane structure including multiple layers of ceramic electrolyte membranes, or a composite membrane structure including a ceramic electrolyte membrane and a polymer electrolyte membrane, which is not limited here.
[0067] Specifically, compared with polymer electrolytes, oxide solid electrolytes have higher ionic conductivity, wider electrochemical stability window, good thermal stability, chemical stability and mechanical strength, which are beneficial to improving the performance of ceramic electrolyte membranes. Optionally, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium gallium oxide (LLZGO) and lithium lanthanum zirconium tantalum oxide (LLZTO). Among them, LLZO is garnet type, and the chemical formula is Li7La3Zr2O 12 LLZGO is LLZO doped with Ga, and LLZTO is LLZO doped with Ta.
[0068] The above-mentioned additives mainly refer to additives used to improve the ionic conductivity of the ceramic electrolyte membrane. In detail, the additive is dispersed in the oxide solid electrolyte, and the additive includes at least one of a first additive and a second additive. Exemplarily, the additive includes a first additive, or the additive includes a second additive, or the additive includes a first additive and a second additive. Among them, the first additive includes at least one of polyvinylidene fluoride and a copolymer of polyvinylidene fluoride. The copolymer of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride has a high dielectric constant, which is beneficial to enhance the ion transportability of the ceramic electrolyte membrane. As an example, the copolymer of polyvinylidene fluoride includes polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The second additive includes a lithium salt and an ionic liquid (abbreviated as lithium salt + ionic liquid). The lithium salt can increase the lithium salt content in the ceramic electrolyte membrane, making the ionic conductivity of the ceramic electrolyte membrane higher. The ionic liquid itself has a high ionic conductivity and can also improve the ionic conductivity of the ceramic electrolyte membrane. As an example, the lithium salt includes at least one of lithium bis(trifluoromethyl)sulfonyl imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(perfluoroethylsulfonyl)imide (LIBETI) and lithium bis(oxalate)borate (LiBOB). As an example, the ionic liquid is a pyrrole ionic liquid, such as N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt ionic liquid. Optionally, in the second additive, the mass ratio of the lithium salt to the ionic liquid is (1.5~2.5):1. For example, the mass ratio of the lithium salt to the ionic liquid is 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1.
[0069] In the embodiment of the present application, polytetrafluoroethylene (PTFE) is a binder. Generally, in the ceramic electrolyte membrane, the content of polytetrafluoroethylene should not be too high, otherwise it is not conducive to the transmission of ions in the ceramic electrolyte membrane, and the content of polytetrafluoroethylene should not be too low, otherwise the mechanical strength of the ceramic electrolyte membrane will decrease, or even the film cannot be formed. In the embodiment of the present application, based on the total mass of the ceramic electrolyte membrane, the content of polytetrafluoroethylene is 0.49wt%~5.03wt%. Within this range, the ceramic electrolyte membrane can form a good film and has both good mechanical strength and ionic conductivity. As an example, the content of polytetrafluoroethylene is 0.49wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.03wt%. In addition, if the content of polytetrafluoroethylene in the ceramic electrolyte membrane is too high, it is easy to cause side reactions after the ceramic electrolyte membrane is assembled into a solid-state battery, resulting in a decrease in the cycle performance of the solid-state battery.
[0070] In some embodiments, based on the total mass of the ceramic electrolyte membrane, the content of the oxide solid electrolyte is 80wt% to 92wt%. Generally, the mechanical strength and ionic conductivity of the ceramic electrolyte membrane increase with the increase of the content of the oxide solid electrolyte, but the excessive content of the oxide solid electrolyte will cause the content of other components to decrease, and the final result is that the performance of the ceramic electrolyte membrane deteriorates. As an example, the content of the oxide solid electrolyte is 80wt%, 82wt%, 84wt%, 86wt%, 88wt%, 90wt% or 92wt%.
[0071] In some embodiments, based on the total mass of the ceramic electrolyte membrane, the content of the first additive is 2.29wt%~5.71wt%, and the content of the second additive is 1.71wt%~4.29wt%. The first additive and the second additive are mainly used to improve the ionic conductivity of the ceramic electrolyte membrane. As an example, the content of the first additive is 2.29wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt% or 5.71wt%; the content of the second additive is 1.71wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt% or 4.29wt%.
[0072] In some embodiments, based on the total mass of the ceramic electrolyte membrane, the content of carboxymethyl cellulose is 2.86wt%~7.14wt%. Carboxymethyl cellulose is mainly used to assist film formation and improve the ductility of the film material during the subsequent rolling process. As an example, the content of carboxymethyl cellulose is 2.86wt%, 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt% or 7.14wt%.
[0073] In some embodiments, the thickness of the ceramic electrolyte membrane is 20 μm to 40 μm. As an example, the thickness of the ceramic electrolyte membrane is 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0074] In some embodiments, the solid electrolyte membrane also includes a polymer electrolyte membrane, which is located on one side surface of the ceramic electrolyte membrane. When the above-mentioned solid electrolyte membrane is applied to a solid-state battery, the polymer electrolyte membrane can be matched with the negative electrode of the solid-state battery. Compared with the ceramic electrolyte membrane, the polymer electrolyte membrane has good flexibility and can effectively construct a stable negative electrode-electrolyte interface, while the ceramic electrolyte membrane corresponds to the positive electrode of the solid-state battery. Due to the high voltage window of the ceramic electrolyte membrane, the deterioration of the positive electrode interface under the high voltage of the positive electrode can be effectively alleviated. Therefore, the solid electrolyte membrane formed by combining the polymer electrolyte membrane with the ceramic electrolyte membrane helps to improve the cycle stability of the solid-state battery. Optionally, the thickness of the polymer electrolyte membrane is 10μm~20μm. As an example, the thickness of the polymer electrolyte membrane is 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0075] The solid electrolyte membrane provided in the embodiment of the present application includes a ceramic electrolyte membrane, which includes an oxide solid electrolyte, an additive and polytetrafluoroethylene, wherein the additive includes at least one of lithium salt + ionic liquid, polyvinylidene fluoride and a copolymer of polyvinylidene fluoride, and the additive is dispersed in the oxide solid electrolyte, which can effectively construct an ion transmission channel and improve the ionic conductivity of the ceramic electrolyte membrane; polytetrafluoroethylene is used as a binder, and by controlling the content of polytetrafluoroethylene in the total material to 0.49wt%~5.03wt%, it can not only ensure film formation but also help to improve the mechanical strength of the ceramic electrolyte membrane.
[0076] In a third aspect, an embodiment of the present application also provides an all-solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte membrane, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode, and the solid electrolyte membrane is the above-mentioned solid electrolyte membrane.
[0077] The above-mentioned solid electrolyte membrane has better ionic conductivity and mechanical strength, which is beneficial to improving the performance of all-solid-state batteries.
[0078] The following describes it in detail with reference to specific embodiments.
[0079] Example 1
[0080] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0081] 0.05 g of CMC (carboxymethyl cellulose) (content 7.14 wt%) was added to 0.56 g of LLZGO (content 80 wt%) powder, and after grinding and mixing, 0.04 g of PVDF (polyvinylidene fluoride) (content 5.71 wt%) was added, and after grinding and mixing, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred and evenly prepared in a ratio of 2:1) (content 4.29 wt%) was added and ground and mixed evenly; finally, 0.02 g of PTFE (content 2.86 wt%) was added, and the mixture was fully ground and mixed to be fiberized to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70°C to obtain a ceramic electrolyte membrane.
[0082] Example 2
[0083] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0084] 0.05 g of CMC (carboxymethyl cellulose) (content 4.81 wt%) was added to 0.9 g of LLZGO (content 86.54 wt%) powder, and 0.04 g of PVDF (polyvinylidene fluoride) (content 3.85 wt%) was added after grinding and mixing evenly, and then 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred evenly in a ratio of 2:1) (content 2.88 wt%) was added after grinding and mixing evenly; finally, 0.02 g of PTFE (content 1.92 wt%) was added, and the mixture was fully ground and mixed to fiberize to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70 ° C to obtain a ceramic electrolyte membrane.
[0085] Example 3
[0086] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0087] 0.05 g of CMC (carboxymethyl cellulose) (content 2.86 wt%) was added to 1.61 g of LLZGO (content 92 wt%) powder, and after grinding and mixing, 0.04 g of PVDF (polyvinylidene fluoride) (content 2.29 wt%) was added, and after grinding and mixing, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred and evenly prepared in a ratio of 2:1) (content 1.71 wt%) was added, and grinding and mixing were uniform; finally, 0.02 g of PTFE (content 1.14 wt%) was added, and the mixture was fully ground and mixed to be fiberized to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70°C to obtain a ceramic electrolyte membrane.
[0088] Example 4
[0089] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0090] 0.05 g of CMC (carboxymethyl cellulose) (content 4.66 wt%) was added to 0.9 g of LLZGO (content 83.8 wt%) powder, and after grinding and mixing, 0.04 g of PVDF (polyvinylidene fluoride) (content 3.72 wt%) was added, and after grinding and mixing, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred and evenly prepared in a ratio of 2:1) (content 2.79 wt%) was added, and grinding and mixing were uniform; finally, 0.054 g of PTFE (content 5.03 wt%) was added, and the mixture was fully ground and mixed to be fiberized to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70 ° C to obtain a ceramic electrolyte membrane.
[0091] Example 5
[0092] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0093] 0.05 g of CMC (carboxymethyl cellulose) (content 4.88 wt%) was added to 0.9 g of LLZGO (content 87.8 wt%) powder, and after grinding and mixing evenly, 0.04 g of PVDF (polyvinylidene fluoride) (content 3.9 wt%) was added, and after grinding and mixing evenly, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred evenly in a ratio of 2:1) (content 2.93 wt%) was added, and grinding and mixing evenly; finally, 0.005 g of PTFE (content 0.49 wt%) was added, and the mixture was fully ground and mixed to be fiberized to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70 ° C to obtain a ceramic electrolyte membrane.
[0094] Example 6
[0095] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0096] 0.04 g of PVDF (polyvinylidene fluoride) (content 4.04 wt%) was added to 0.9 g of LLZGO (content 90.91 wt%) powder, and after grinding and mixing evenly, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred evenly in a ratio of 2:1) (content 3.03 wt%) was added and ground and mixed evenly; finally, 0.02 g of PTFE (content 2.02 wt%) was added, and the mixture was fully ground and mixed to fiberize to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70°C to obtain a ceramic electrolyte membrane.
[0097] Example 7
[0098] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0099] 0.05 g of CMC (carboxymethyl cellulose) (content 5wt%) was added to 0.9 g of LLZGO (content 90wt%) powder, and after grinding and mixing evenly, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred evenly in a ratio of 2:1) (content 3wt%) was added and ground and mixed evenly; finally, 0.02 g of PTFE (content 2wt%) was added, and the mixture was fully ground and mixed to fiberize to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70°C to obtain a ceramic electrolyte membrane.
[0100] Example 8
[0101] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0102] 0.05 g of CMC (carboxymethyl cellulose) (content 4.95 wt%) was added to 0.9 g of LLZGO (content 89.11 wt%) powder, and after grinding and mixing evenly, 0.04 g of PVDF (polyvinylidene fluoride) (content 3.96 wt%) was added, and grinding and mixing evenly; finally, 0.02 g of PTFE (content 1.98 wt%) was added, and the mixture was thoroughly ground and mixed to fiberize to obtain a flaky mixture; the flaky mixture was rolled on a roller press at 70°C to obtain a ceramic electrolyte membrane.
[0103] Comparative Example 1
[0104] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0105] 0.05 g of CMC (carboxymethyl cellulose) (content 4.81 wt%), 0.04 g of PVDF (polyvinylidene fluoride) (content 3.85 wt%), 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI are stirred evenly in a ratio of 2:1) (content 2.88 wt%) and 0.02 g of PTFE (content 1.92 wt%) are added to 0.9 g of LLZGO (content 86.54 wt%) powder, and the mixture is fully ground and mixed to obtain a mixture; the mixture is rolled in a roller press at 70 ° C to obtain a ceramic electrolyte membrane.
[0106] Comparative Example 2
[0107] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0108] 0.05 g of CMC (carboxymethyl cellulose) (content 4.61 wt%) was added to 0.9 g of LLZGO (content 82.95 wt%) powder, and after grinding and mixing evenly, 0.04 g of PVDF (polyvinylidene fluoride) (content 3.69 wt%) was added, and after grinding and mixing evenly, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred evenly in a ratio of 2:1) (content 2.76 wt%) was added, and grinding and mixing evenly; finally, 0.065 g of PTFE (content 5.99 wt%) was added, and the mixture was fully ground and mixed to be fiberized to obtain a flaky mixture; the flaky mixture was rolled in a roller press at 70°C to obtain a ceramic electrolyte membrane.
[0109] Comparative Example 3
[0110] The ceramic electrolyte membrane is prepared by a dry forming process, including:
[0111] 0.05 g of CMC (carboxymethyl cellulose) (content 4.88 wt%) was added to 0.9 g of LLZGO (content 87.89 wt%) powder, and after grinding and mixing evenly, 0.04 g of PVDF (polyvinylidene fluoride) (content 3.91 wt%) was added, and after grinding and mixing evenly, 0.03 g of LiTFSI-IL mixed solution (N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide ionic liquid and LiTFSI were stirred evenly in a ratio of 2:1) (content 2.93 wt%) was added, and grinding and mixing evenly; finally, 0.004 g of PTFE (content 0.39 wt%) was added, and grinding and mixing were fully performed. Due to the small amount of PTFE, a flaky mixture could not be obtained.
[0112] The mass and mass percentage of each material in the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1:
[0113] Table 1
[0114]
[0115] The ceramic electrolyte membranes provided in Examples 1 to 8 and Comparative Examples 1 to 2 were characterized as follows:
[0116] 1. Ionic conductivity test:
[0117] The ionic conductivity of the ceramic electrolyte membranes prepared in Examples 1 to 8 and Comparative Examples 1 to 2 was tested. The specific testing method is as follows: The impedance of the solid electrolyte is tested by an electrochemical workstation. Pt is sputtered on the surface of the solid electrolyte and tested by electrochemical impedance spectroscopy (EIS) with a frequency range of 105 Hz to 0.1 Hz. The ionic conductivity is calculated by the formula: σ=L / RA, where L represents the thickness of the electrolyte, R represents the impedance, and A represents the effective contact area. The test results are recorded in Table 2.
[0118] 2. Electrochemical window test:
[0119] The ceramic electrolyte membranes prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to electrochemical window tests. The specific test method is as follows: the solid electrolyte is sandwiched between a steel sheet and a lithium foil, and the test is performed using a linear voltammetry (LSV) method with a scan voltage range of 2.0 V to 6.0 V and a scan rate of 1 mVs -1 The results are shown in Table 2.
[0120] 3. Cycle performance test:
[0121] First, prepare the solid-state battery according to the following steps:
[0122] (1) Preparation of positive electrode sheet: Nickel cobalt manganese oxide (NCM) powder, super P and PVDF were mixed in NMP solvent in a mass ratio of 8:1:1, and magnetic stirring was performed to obtain positive electrode slurry. The NCM positive electrode slurry was evenly scraped onto the aluminum foil current collector by the cast coating method, and then vacuum dried at 110 °C for 48 h. In order to facilitate battery assembly, the prepared positive electrode sheet was cut into discs with a diameter of 12 mm. The active material loading of the NCM positive electrode was 11.5 mg cm -2 .
[0123] (2) Preparation of negative electrode sheet: Purchase lithium sheets and cut them into discs with a diameter of 12 mm.
[0124] (3) Battery assembly: In this study, a CR2032 battery shell was used to assemble button cells, and a punched aluminum-plastic film was used to assemble soft-pack batteries. The battery assembly was carried out in a glove box filled with argon gas. The assembly order of button cells was: positive electrode shell, positive electrode sheet, solid electrolyte, lithium foil, steel sheet, shrapnel, negative electrode shell. After the battery assembly was completed, it was packaged using a button battery packaging machine. The soft-pack battery assembly process is to sandwich the electrolyte between the positive electrode sheet and the lithium ribbon, attach aluminum and nickel tabs to the positive and negative electrodes respectively, put them into the punched aluminum-plastic film, and complete the packaging using a vacuum packaging machine.
[0125] The ceramic electrolyte membranes prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were respectively prepared into solid-state batteries according to the above-mentioned method for preparing solid-state batteries, and the corresponding solid-state batteries were subjected to cycle performance tests. The specific test method is as follows: the solid-state batteries were subjected to cycle performance tests at 26°C with the charge and discharge cut-off voltage set to 3.0V~4.2V and the charge and discharge rate set to 0.33C / 1C. The number of cycles when the capacity retention rate reached 80% was counted, and the results are recorded in Table 2.
[0126] 4. Tensile strength test:
[0127] The ceramic electrolyte membranes prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to a tensile strength test. The specific test method is as follows: the national standard adopted for the electrolyte tensile test is the plastic film tensile performance test method GB 13022-91. Before the test, the sample was placed in an environment with a temperature of 23°C and a humidity of 50% for 24 hours. The stretching rate was 50 mm / min. The results are recorded in Table 2.
[0128] Table 2
[0129]
[0130] 5. Scanning electron microscope test:
[0131] The ceramic electrolyte membranes prepared in Example 2 and Comparative Example 1 were photographed using a scanning electron microscope. Figure 2 The scanning electron microscope image of the ceramic electrolyte membrane of Example 2 of the present application is shown. Figure 2 It can be seen that there are fewer large particles in the membrane layer, fewer holes in the membrane layer, and the density of the membrane layer is better; Figure 3 The SEM image of the ceramic electrolyte membrane of Comparative Example 1 of the present application is shown. Figure 3 It can be seen that there are more large particles in the membrane layer, more holes in the membrane layer, and the density of the membrane layer is poor.
[0132] Combining Table 1 and Table 2 for analysis, by comparing Examples 1 to 3, it can be seen that when the mass of other materials remains unchanged, by increasing the mass of LLZGO (0.56g, 0.9g, 1.61g respectively), the mass percentage of LLZGO in the ceramic electrolyte membrane increases (80wt%, 86.54wt%, 92wt% respectively), and the ionic conductivity, electrochemical window, number of cycles and tensile strength of the ceramic electrolyte membrane all increase first and then decrease, among which the performance of the ceramic electrolyte membrane provided in Example 2 is the best. This is because LLZGO itself has a wider electrochemical outlet, better ionic conductivity and mechanical strength. Within a certain range, an increase in the content of LLZGO can promote the improvement of the performance of the ceramic electrolyte membrane, but an excessive content of LLZGO will cause the content of other materials in the ceramic electrolyte membrane to decrease, thereby causing the performance of the ceramic electrolyte membrane to decrease. This shows that the performance of the ceramic electrolyte membrane is the result of the combined effect of each component.
[0133] By comparing Comparative Example 3, Example 5, Example 2, Example 4 and Comparative Example 2, it can be seen that when the mass of other materials remains unchanged, by increasing the mass of PTFE (respectively 0.004g, 0.005g, 0.02g, 0.054g, 0.065g), the mass percentage content of PTFE increases (0.39wt%, 0.49wt%, 1.92wt%, 5.03wt%, 5.99wt%), among which except for Comparative Example 3, which cannot form a film due to the low content of PTFE, the others can form a ceramic electrolyte membrane. Further comparison shows that in terms of mechanical strength, as the mass percentage content of PTFE increases, the tensile strength of the ceramic electrolyte membrane gradually increases. This is because the cohesive force of the ceramic electrolyte membrane increases after the content of PTFE increases, which improves the mechanical strength of the ceramic electrolyte membrane. In terms of ionic conductivity, as the mass percentage content of PTFE decreases, the ionic conductivity of the ceramic electrolyte membrane first increases and then decreases. This is because as the content of PTFE decreases, the content of LLZGO, PVDF and LiTFSI-IL increases, thereby improving the ionic conductivity of the ceramic electrolyte membrane; the ionic conductivity of the ceramic electrolyte membrane in Example 5 decreases because the mass percentage content of PTFE is low, the cohesion of the ceramic electrolyte membrane is insufficient, and the bonding between the particles is not tight enough, resulting in the ion transmission channel in the ceramic electrolyte membrane being affected, and the ionic conductivity of the ceramic electrolyte membrane is reduced. In terms of electrochemical window, as the mass percentage content of PTFE increases, the electrochemical window of the ceramic electrolyte membrane first increases and then decreases, but the overall value is relatively close and does not change much. This is because the electrochemical window of the ceramic electrolyte membrane is mainly affected by the main material LLZGO. Since the content of LLZGO in each ceramic electrolyte membrane is not much different, the electrochemical window does not change significantly. In addition, in terms of cycle performance, as the mass percentage content of PTFE increases, the number of cycles of the ceramic electrolyte membrane first increases and then decreases. This is because as the mass percentage content of PTFE increases, the mechanical strength of the ceramic electrolyte membrane increases and the number of cycles of the ceramic electrolyte membrane increases. However, if the mass percentage content of PTFE is too high, side reactions in the solid-state battery will increase, which will in turn cause the cycle performance of the solid-state battery to decrease.
[0134] By comparing Example 2 and Example 6, it can be seen that the difference between the two is that Example 6 does not contain CMC. It is found that the ionic conductivity of the ceramic electrolyte membrane in Example 6 is slightly decreased, but the tensile strength and cycle number of the ceramic electrolyte membrane are significantly decreased. This is because CMC can improve the ductility of the membrane material during the preparation process of the ceramic electrolyte membrane, and ultimately improve the film quality of the ceramic electrolyte membrane.
[0135] Comparing Example 2 and Example 7, it can be seen that the difference between the two is that Example 7 does not contain PVDF. As a result, it is found that the ionic conductivity, mechanical strength and number of cycles of the ceramic electrolyte membrane in Example 7 are all reduced.
[0136] Comparing Example 2 and Example 8, it can be seen that the difference between the two is that Example 8 does not contain LiTFSI-IL. It is found that the ionic conductivity of the ceramic electrolyte membrane in Example 8 decreases significantly, which indicates that LiTFSI-IL has a significant promoting effect on improving the ionic conductivity of the ceramic electrolyte membrane. In addition, the mechanical strength and cycle number of the ceramic electrolyte membrane in Example 8 also decrease, because the ionic liquid can provide more ions for the electrolyte system to migrate, and the small number of ions when the ionic liquid is not added will affect the cycle performance of the system; at the same time, the ionic liquid also has the function of wetting the system. Not adding the ionic liquid will cause the entire system to be dry and the strength will be reduced.
[0137] Comparing Example 2 and Comparative Example 1, it can be seen that the difference between the two is only the difference in the preparation process. In Example 2, CMC, PVDF, and LiTFSI are added to LLZGO in batches and ground and mixed, and PTFE is added and ground and mixed at last. In Comparative Example 1, CMC, PVDF, LiTFSI, and PTFE are added to LLZGO at one time and ground and mixed. The results show that the ionic conductivity, mechanical strength, and number of cycles of the ceramic electrolyte membrane in Example 2 are significantly higher than those of the ceramic electrolyte membrane in Comparative Example 1. Figure 2 and Figure 3 It can be seen that the uniformity and density of the ceramic electrolyte membrane obtained in Example 2 are better. This is because in the preparation process of Comparative Example 1, since LLZGO, CMC, PVDF, LiTFSI and PTFE are mixed together and then ground together, PTFE will be fiberized during the grinding process, so that other materials are bonded together without being fully refined and dispersed, resulting in a decrease in the ionic conductivity and mechanical strength of the ceramic electrolyte membrane, and then the cycle performance is also reduced.
[0138] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: include: Performing a first grinding and mixing process on the oxide solid electrolyte and the additive to obtain a first mixture, wherein the additive includes a first additive and a second additive, the first additive includes at least one of polyvinylidene fluoride and a copolymer thereof, and the second additive includes a lithium salt and an ionic liquid, wherein the lithium salt is dissolved in the ionic liquid; The first mixture and polytetrafluoroethylene are subjected to a second grinding and mixing process to obtain a flake mixture, wherein the content of the polytetrafluoroethylene is 0.49wt% to 5.03wt% based on the total mass of the flake mixture; Rolling the sheet-like mixed material to obtain a ceramic electrolyte membrane, wherein the solid electrolyte membrane includes the ceramic electrolyte membrane; The step of subjecting the oxide solid electrolyte and the additive to a first grinding and mixing process to obtain a first mixture comprises: Grinding and mixing the oxide solid electrolyte and the first additive to obtain a dry mixture; After dissolving the lithium salt in the ionic liquid to obtain the second additive, the dry mixture and the second additive are ground and mixed to obtain the first mixture; the preparation process of the dry mixture further includes: Grinding and mixing the oxide solid electrolyte and carboxymethyl cellulose; Based on the total mass of the flaky mixture, the content of the oxide solid electrolyte is 80wt%~92wt%, the content of the first additive is 2.29wt%~5.71wt%, the content of the second additive is 1.71wt%~4.29wt%, and the content of the carboxymethyl cellulose is 2.86wt%~7.14wt%; in the second additive, the lithium salt includes lithium bis(trifluoromethyl)sulfonyl imide, the ionic liquid includes N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, and the mass ratio of the lithium bis(trifluoromethyl)sulfonyl imide to the N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide is (1.5~2.5):
1.
2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium gallium oxide and lithium lanthanum zirconium tantalum oxide; And / or, the temperature of the roller pressing treatment is 50° C. to 100° C., and the roller pressing pressure is 15t to 40t.
3. The method for preparing a solid electrolyte membrane according to any one of claims 1 to 2, characterized in that: The method for preparing the solid electrolyte membrane also includes preparing a polymer electrolyte membrane by a wet forming process, and arranging the polymer electrolyte membrane on one side surface of the ceramic electrolyte membrane.
4. A solid electrolyte membrane, characterized in that: The ceramic electrolyte membrane comprises an oxide solid electrolyte, an additive and polytetrafluoroethylene, wherein the additive comprises a first additive and a second additive, wherein the first additive comprises at least one of polyvinylidene fluoride and a copolymer of polyvinylidene fluoride, and the second additive comprises a lithium salt and an ionic liquid, wherein the lithium salt is dissolved in the ionic liquid, and the content of the polytetrafluoroethylene is 0.49wt% to 5.03wt% based on the total mass of the ceramic electrolyte membrane; the ceramic electrolyte membrane further comprises carboxymethyl cellulose, and the content of the oxide solid electrolyte is 80wt% based on the total mass of the ceramic electrolyte membrane. %~92wt%, the content of the first additive is 2.29wt%~5.71wt%, the content of the second additive is 1.71wt%~4.29wt%, and the content of the carboxymethyl cellulose is 2.86wt%~7.14wt%; in the ceramic electrolyte membrane, the lithium salt includes lithium bis(trifluoromethyl)sulfonyl imide, the ionic liquid includes N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, and the lithium salt includes a mass ratio of lithium bis(trifluoromethyl)sulfonyl imide to the N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (1.5~2.5):
1.
5. The solid electrolyte membrane according to claim 4, characterized in that The oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium gallium oxide and lithium lanthanum zirconium tantalum oxide; And / or, the ceramic electrolyte membrane has a thickness of 20 μm to 40 μm.
6. The solid electrolyte membrane according to claim 4, characterized in that The solid electrolyte membrane further comprises a polymer electrolyte membrane, which is located on one side surface of the ceramic electrolyte membrane. The thickness of the polymer electrolyte membrane is 10 μm to 20 μm.
7. An all-solid-state battery, characterized in that: It comprises a positive electrode, a negative electrode and a solid electrolyte membrane, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode, and the solid electrolyte membrane is prepared according to the preparation method of the solid electrolyte membrane according to any one of claims 1 to 3 or is the solid electrolyte membrane according to any one of claims 4 to 6.
Citation Information
Patent Citations
Composite electrolyte, preparation method thereof and lithium ion battery
CN115189016A
Composite electrode plate, preparation method thereof and lithium ion battery
CN117117101A
Composition, ceramic electrolyte thin film, preparation method of ceramic electrolyte thin film, composite thin film and application of composite thin film
CN118156589A